2018
DOI: 10.5751/es-09844-230114
|View full text |Cite
|
Sign up to set email alerts
|

The climate-smart village approach: framework of an integrative strategy for scaling up adaptation options in agriculture

Abstract: ABSTRACT. Increasing weather risks threaten agricultural production systems and food security across the world. Maintaining agricultural growth while minimizing climate shocks is crucial to building a resilient food production system and meeting developmental goals in vulnerable countries. Experts have proposed several technological, institutional, and policy interventions to help farmers adapt to current and future weather variability and to mitigate greenhouse gas (GHG) emissions. This paper presents the cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
146
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 170 publications
(149 citation statements)
references
References 26 publications
0
146
0
3
Order By: Relevance
“…Based on the principles of participatory action research, the CSV approach enables farmers to pick practices and technologies that meet their local specific needs and allows drawing lessons on agricultural technologies and practices to inform policy decisions from local to global levels [5]. The paper by Aggarwal et al [5] provides a comprehensive overview of the CCAFS CSV approach.In Mali, the CSV approach has since 2011 been used to test and validate many CSA technologies and practices (including drought tolerant crop varieties, micro-dosing, organic manure, intercropping, contour farming, farmer managed natural regeneration, agroforestry and climate information services) with the participation of farmers. Several authors have reported successful results of CSA technologies tested and their implications for local food security [6-9] and income [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the principles of participatory action research, the CSV approach enables farmers to pick practices and technologies that meet their local specific needs and allows drawing lessons on agricultural technologies and practices to inform policy decisions from local to global levels [5]. The paper by Aggarwal et al [5] provides a comprehensive overview of the CCAFS CSV approach.In Mali, the CSV approach has since 2011 been used to test and validate many CSA technologies and practices (including drought tolerant crop varieties, micro-dosing, organic manure, intercropping, contour farming, farmer managed natural regeneration, agroforestry and climate information services) with the participation of farmers. Several authors have reported successful results of CSA technologies tested and their implications for local food security [6-9] and income [10].…”
mentioning
confidence: 99%
“…The CSV approach enables ground-breaking research on agricultural technologies and practices to define their potential to deliver on the food security, adaptation and mitigation goals of CSA. Based on the principles of participatory action research, the CSV approach enables farmers to pick practices and technologies that meet their local specific needs and allows drawing lessons on agricultural technologies and practices to inform policy decisions from local to global levels [5]. The paper by Aggarwal et al [5] provides a comprehensive overview of the CCAFS CSV approach.…”
mentioning
confidence: 99%
“…The general call for climate change adaptation, and particularly for agricultural adaptation management, makes it pertinent to understand the complexity of adaptation decision-making-in order to manage adaptation in a sustainable manner (e.g. Aggarwal et al 2018). This study's scientific contribution lies in addressing the current lack of studies focusing on adaptation trade-offs as well as to support theoretical development in the field.…”
Section: Discussionmentioning
confidence: 99%
“…There is a recognized need to seize adaptation synergies and minimize trade-offs in the implementation of sustainability policies and measures in order to create climate resilient pathways (Aggarwal et al 2018;Roy et al 2018). Adaptation measures that potentially involve maladaptation (Juhola et al 2016;Magnan et al 2016) inherently also involve a trade-off between the intended positive effect of the adaptation measure and the unintended negative outcome.…”
Section: Introductionmentioning
confidence: 99%
“…In this and other cases, CSA practices and technologies have been found to improve productivity and income for participating farmers while reducing risks, but contributions of the CSA approach to gender equality and empowerment within households are not well understood. In some cases, CSA may entrench gender inequalities, while in others, women's empowerment is a factor in CSA adoption (see Aggarwal et al 2018;Haapala 2018;Mutenje et al 2019). The second group of articles in this issue explores methodologies and approaches to address this knowledge gap.…”
mentioning
confidence: 99%